Injury/Illness Physician Referral Profile From a Youth University-Sponsored Summer Sport Camp Program. (August 2013) - Oller, Daria M.; Vairo, Giampietro L.; Sebastianelli, Wayne J.; Buckley, William E.
Participation at university-sponsored summer sport camps is popular among youth athletes; however, there is a dearth of information to describe the injuries/illnesses experienced by camp participants. Data from a university-sponsored sport camp program from 2008 to 2011 were accessed retrospectively. The sport camp program had approximately 80 camps for 28 sports over 12 weeks annually. Male and female participants were 10 to 17 years old. Athletic trainers maintained medical documentation and provided medical referrals. Referrals were made for 9.9% (n = 478) of all injuries/illnesses. Emergency department referrals were made for 2.9% of injuries/illnesses. University health services received 42.5% of referrals. There were 1.1 referrals per 100 participants. Boys comprised 60.7% of referrals. Rugby had the highest referral rate—5.0 per 100 participants. These data help increase physician preparedness and guide the delivery of sports medicine services for related sport camp programs as a means to improve quality of care delivered to participants.